Advances in accounting behavioral research - Karim, Khondkar E. (Emerald Publishing Limited, 2024)
Focusing on research that examines both individual and organizational behavior relative to accounting, Advances in Accounting Behavioral Research provides an in-depth analysis and exchange of peer-reviewed knowledge across all areas of accounting behavioral research and the development, discussion, and expansion of theories from psychology, sociology, and related disciplines. The theme of Volume 28 is emerging theory, methods, and applications towards behavioral research in accounting and audit. Chapters collected here examine topics ranging from CFO ethnicity and impact on financial reporting to career imprinting to safeguards in crowdfunding and more.
Keywords: Accounting -- Research.; Organizational behavior -- Research.; Financial statements -- Research.; Business & Economics -- Accounting -- Financial.; Financial reporting, financial statements.; Financial accounting.; elektronické knihy; electronic books